DOCUMENTATION OF ETHNOVETERINARY PRACTICES IN DISTRICT JHANG, PAKISTAN - N. Badar1.; Z. Iqbal; M. S. Sajid; H. M. Rizwan; A. Jabbar; W. Babar; M. N. Khan; A. Ahmed (Journal of Animal and Plant Sciences, 2017)
The study was conducted to document the plants used in the traditional veterinary practices in Jhang district of Pakistan. Rapid and participatory rural appraisal techniques were used for collection of information i.e. the interviews and focused group discussions were carried with 253 traditional veterinary healers for a period of one year. From the study area, 46 plant species representing 31 families were documented for the treatment of different infectious and non-infectious ailments. The most frequently reported (≥ 22% respondents) plants included: Trachyspermum ammi (L.) Sprague, Capsicum annuum Linn, Vernonia anthelmintica L., Foeniculum vulgare Mill, and Allium cepa Linn. Of 46 plants, 33 were indigenous. Materials other than plants are also used as adjunctive therapy for different ailments. A wide variation in the dose, vehicle, part of plant, mode of preparation and administration/application was observed. The efficacy claims and indications for different plants were quite conflicting. The traditional veterinary healers in the study area used diverse plant species in the veterinary practices with varying claims about their efficacies. Controlled studies for the validation of the plant usage are underway in the Department of Parasitology, University of Agriculture, Faisalabad, Pakistan.
Keywords: Ethno-veterinary; Phytotherapy; Medicinal plants; Documentation; Jhang; Pakistan